2014
DOI: 10.1007/s11746-014-2510-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Acid Value on TBHQ and BHT Losses in Heating Oils: Identification of the Esterification Products of TBHQ and Free Fatty Acids

Abstract: The loss of phenolic antioxidants is one of the major problems associated with the food frying process. As temperature increases and heating time is prolonged, losses of both tertiary butylhydroquinone (TBHQ) and butylated hydroxytoluene (BHT) are significantly increased. In this work, the effect of different types of free fatty acids (FFA) and the acid value (AV) of soybean oil (SBO) on TBHQ and BHT losses during heating were systematically studied. The results showed that the higher the AV of SBO at 120 or 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 12 publications
3
23
0
Order By: Relevance
“…This indicated that TBHQ itself was the main volatilization product of TBHQ in PO under the heating condition. Similar results were reported by Li et al 20 . Several transformation and decomposition products were also observed in volatilization products.…”
Section: Identi Cation Of Volatilization Products Of Tbhq In Posupporting
confidence: 92%
See 1 more Smart Citation
“…This indicated that TBHQ itself was the main volatilization product of TBHQ in PO under the heating condition. Similar results were reported by Li et al 20 . Several transformation and decomposition products were also observed in volatilization products.…”
Section: Identi Cation Of Volatilization Products Of Tbhq In Posupporting
confidence: 92%
“…The extraction procedure was as followings 20 : 2.00 g of each of melted oil samples was weighed into a 10 mL test tube, and 4 mL of methanol was added. The mixture was agitated for 2 min using a vortex mixer and then centrifuged at 2,000 rpm for 2 min at room temperature.…”
Section: Extraction Proceduresmentioning
confidence: 99%
“…Similar phenomenon occurred about tertiary butylhydroquinone (TBHQ) and butylated hydroxytoluene (BHT) losses [25,26], which were mainly attributable to the volatilization and transformation of TBHQ and BHT during heating [27]. According the previous reports [25,26], we hypothesized that gossypol losses might be due to the volatilization and transformation of gossypol.…”
Section: Statistical Analysessupporting
confidence: 68%
“…These results suggested that gossypol losses were attributed to the transformation of gossypol. And the effect of volatilization on gossypol losses can be negligible, which were different from that (evaporation) of BHT and TBHQ losses at higher temperatures. These differences might be ascribed to the higher molecular weight (518) and boiling point (707°C) of gossypol than those of BHT (MV, 220; b.p., 265°C) and TBHQ (MV, 166; b.p., 295°C).…”
Section: Resultsmentioning
confidence: 75%
See 1 more Smart Citation